High efficiency adsorption of hexavalent chromium using bioderived activated carbon kinetics, isotherms, and thermodynamics - W. A. Hammad; Samah A. Hawash; Mohamed S. Abdel-latif; Mohammed Kuku; M. H. A. Amr (Scientific Reports)
Abstract Hexavalent chromium (Cr6+), a toxic pollutant in industrial wastewater, poses serious environmental and health risks. This study investigates H₃PO₄-treated palm frond-derived activated carbon (PFTACs) as a low-cost, sustainable adsorbent for Cr6+ removal. PFTACs achieved 99.64% removal efficiency within 90 min at 25 ± 1 °C, with strong performance across a pH range of 2–8. Surface analyses confirmed its mesoporous structure and high surface area, while FT-IR indicated physical adsorption as the dominant mechanism. The process followed pseudo-second-order kinetics and fitted the Langmuir isotherm, suggesting monolayer adsorption. Thermodynamic analysis showed an exothermic nature, with reduced adsorption at higher temperatures. These findings support PFTACs as an effective and environmentally friendly solution for Cr6+-contaminated water treatment.The novelty of this research lies in the development of H3PO4-treated palm frond-derived activated carbon (PFTACs) as an innovative, sustainable adsorbent for hexavalent chromium (Cr6+) removal. The use of palm fronds, an abundant agricultural waste, offers an eco-friendly and cost-effective alternative to traditional adsorbents, contributing to both waste reduction and efficient pollutant removal in industrial wastewater.